Identidad Y Orientación Sexual: Una Mirada Al Proceso De Asunción Como Sujeto Bisexual (2019)
In the interest to understand the different expressions of sexuality, a tendency to categorize has emerged, which makes it possible to understand other realities from a new perspective, as in the case of bisexuality. That is why this research sought to identify the identity references that most influence the development of personal identity in the process of assumption of bisexual orientation, for this, an investigation was conducted in which 6 people between 18 and 30 years participated from the city of Bogotá, using the technique of autobiographical narratives taken through conversational interviews in which two aspects were investigated; the reactions perceived by family, friends and LGTBI peers, as opposed to the communication of the bisexual choice. Secondly, because of the influence of the heteronormative social framework through the stereotypes associated with labels, since these elements will be the ones that constitute the way of elaboration in relation to each domain of identity.